2016
DOI: 10.1016/j.nuclphysb.2016.08.001
|View full text |Cite
|
Sign up to set email alerts
|

A rotation/magnetism analogy for the quark–gluon plasma

Abstract: In peripheral heavy ion collisions, the Quark-Gluon Plasma that may be formed often has a large angular momentum per unit energy. This angular momentum may take the form of (local) rotation. In many physical systems, rotation can have effects analogous to those produced by a magnetic field; thus, there is a risk that the effects of local rotation in the QGP might be mistaken for those of the large genuine magnetic fields which are also known to arise in these systems. Here we use the gauge-gravity duality to i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 114 publications
(205 reference statements)
0
20
0
Order By: Relevance
“…It may be preferable to turn attention to the exciting prospects opened up by the various beam energy scan experiments currently under way or in preparation [62][63][64][65][66][67], where the QGP is much more likely to be strongly coupled and where, as was explained in [9], there is no difficulty in satisfying the consistency condition even in the presence of large magnetic fields (because the non-zero baryonic chemical potential tends to counteract the tendency of the magnetic field to violate it). A holographic approach may well prove fruitful in that region of the quark matter phase diagram: see for example [68,69] and references therein.…”
Section: Resultsmentioning
confidence: 99%
“…It may be preferable to turn attention to the exciting prospects opened up by the various beam energy scan experiments currently under way or in preparation [62][63][64][65][66][67], where the QGP is much more likely to be strongly coupled and where, as was explained in [9], there is no difficulty in satisfying the consistency condition even in the presence of large magnetic fields (because the non-zero baryonic chemical potential tends to counteract the tendency of the magnetic field to violate it). A holographic approach may well prove fruitful in that region of the quark matter phase diagram: see for example [68,69] and references therein.…”
Section: Resultsmentioning
confidence: 99%
“…However, before finishing this section we would like to make a comment on possibility, in the present relativistic context, of existence of a relation between rotation and (effective) magnetic field which was discussed in the literature recently in refs. [23,28].…”
Section: Rotation Vs External Magnetic Fieldmentioning
confidence: 99%
“…[35]). However, at finite temperature the overall influence of global rotation on the chiral transition is similar to the one of the inverse magnetic catalysis [35]: the critical temperature of the chiral transition is a decreasing function of both temperature and angular frequency [28]. 2 A qualitatively similar effect on the critical temperature may also be produced by a finite chemical potential [23], so that the analogy of the rotation and magnetic field at finite temperature is not clear.…”
Section: Jhep01(2017)136mentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the possibility of a change in the quark-hadron phase transition line in the QCD phase diagram under the combined influence of external magnetic field and local vortices was explored in Ref. [22]; we refer the reader to the recent reviews [23][24][25][26][27], where more details can be found.…”
Section: Introductionmentioning
confidence: 99%